Konseptualisasi Etika dalam Politik: Perspektif Komunikasi Islami - Rasyid, Abdul (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
An ethical system does not solve all the practical issues, but we can not choose and act rationally without a clear system of ethics or vague. An ethical theory does not tell someone what to do in certain situations, but he also is not silent at all; theory of ethics to tell him what should be considered to decide what he should do. Practical functions of an ethics system primarily is to direct our attention to relevant considerations, the reasons that determine the truth or fallacy of action. In this context is required institutionalization and familiarization ethics in politics. For its own pressure groups will try to interpret their interests as public interests, then it is up to the general public to judge.